Evaluating continuous glucose monitoring (CGM) derived glucose variability in athletes clinically diagnosed with relative energy deficiency in sport (REDs) - Matkin-Hussey, P. A.; Baker, D. F.; Cox, G. R.; Coffey, V.; Bowler, A.; Beable, S.; Ogilvie, M.; Black, K. E. (European Journal of Sport Science, 2026)
ABSTRACT Relative Energy Deficiency in Sport (REDs) is a multifactorial condition with significant long-term health and performance implications. Acute low energy availability (LEA) may suppress glucose levels, particularly nocturnally; however, this has not been investigated in athletes with clinically diagnosed REDs. This pilot study examined if glucose variations exist and are detectable using continuous glucose monitoring (CGM) and associations between dietary intake, specifically carbohydrate (CHO) and glucose variability among women athletes with clinically diagnosed REDs compared to matched controls. Eighteen female athletes participated: nine with a clinical REDs diagnosis by a sports physician or reproductive endocrinologist (27.8 ± 6.6 years) and nine matched healthy controls (28.8 ± 7.1 years). Participants recorded 4 days of dietary intake and 7 days of exercise and interstitial glucose data via CGM. No significant group differences were observed in nocturnal mean interstitial glucose (MG) ( p = 0.21) or nocturnal glycaemic variability, assessed by the mean amplitude of glycaemic excursion (MAGE) ( p = 0.92). In the REDs participants, nocturnal MG correlated negatively with CHO intake ( r = -0.698, p = 0.04), whereas controls showed a positive association ( r = 0.536, p = 0.14). An inverse association was also observed for CHO intake and nocturnal MAGE (REDs r = -0.592, p = 0.09; control r = 0.787, p = 0.01, 95% CI 0.26-0.95). In this study, athletes clinically diagnosed with REDs did not exhibit lower glucose concentrations compared to controls, yet opposing associations between CHO intake and glucose metrics suggest distinct metabolic adaptations. In this pilot study, CGM-derived glucose variability measures failed to differentiate athletes with a clinical diagnosis of REDs from healthy controls in free-living settings.